The Role of Nurse in the Multidisciplinary Management of Cancer Cachexia - Yiyuan Zhao; Dong Pang; Yuhan Lu (Elsevier, 2021)
Cancer cachexia is a complex syndrome for which multidisciplinary management through collaboration has the potential to improve patient outcomes and efficiency of care, through the integration of nursing into practice. These authors conducted a literature review of PubMed, EBSCO, OVID, and ProQuest for publications on the roles and responsibilities of nurses who are working in multidisciplinary teams for the management of cancer cachexia. We limited our search parameters for the literature review such that: (1) the included papers were published in the English language from January 2000 to February 2021 and (2) the included papers featured an adult patient population. Based on this review, cancer cachexia can be characterized as an involuntary loss of body weight that is combined with a dysregulation in the control of energy homeostasis and protein loss, which leads to poor clinical outcomes in patients. Cancer cachexia has been recognized as having multidimensional etiologies that are related to the nutritional and metabolic systems, as well as other physical and physiological systems, and to symptoms that manifest concurrently to the cachexia. While the clinical identification and taxonomic classification of cancer cachexia are usually associated with an observable degree of weight loss and muscular atrophy in a patient, clinical evidence of inflammation and related symptoms should be considered (in addition to the weight loss and muscular atrophy) in the diagnosis and evaluation of cancer cachexia, as will be argued in this paper. Early diagnosis, appropriate clinical assessment, and evaluation of cancer cachexia are crucial to predicting the onset of the condition and managing its symptoms when it occurs. Various tools have been developed for the clinical evaluation and diagnosis of cancer cachexia which reflect the multitudinous manifestations of the condition. Due to the diversity of its manifestations, multimodal therapy has gained popularity for the management of cancer cachexia. Multimodal therapy includes combined pharmacologic intervention, nutrition supplements, nutritional consultation, physical exercise, and symptom control. As these authors will demonstrate in this paper, this mode of multidisciplinary team management is increasingly supported by scientific evidence and as such, can be seen as essential for high-quality cancer cachexia management. Nursing plays an important role in the multidisciplinary care team model for cancer cachexia management, as nurses are well situated to perform screening, referral, coordination, nutritional consultation, physical exercise consultation, direct nutritional nursing, psychosocial support, symptom control, and hospice care. However, an increased focus on education, skills training, and tool development (as well as adoption of tools) on the part of nurses and other multidisciplinary team members is required to meet the goal of efficient care and improved outcomes for patients with cancer cachexia. These authors demonstrate that increasing roles and responsibilities for nurses in the management of cancer cachexia is a valuable area to explore in the literature and to implement in clinical practice. Our review aims to summarize the etiology and epidemiology, mechanisms-of-action, and multitudinous manifestations of cancer cachexia, the therapies that are used in cancer cachexia care and the management approaches by which this care is organized. Finally, these authors emphasize nurses' responsibilities in this mode of cancer cachexia multidisciplinary team management, which represents a fruitful benefit both in the research literature and in clinical settings.